Ancient DNA and the human settlement of the Pacific: A review. Issue 79 (February 2015) - Matisoo-Smith, Elizabeth
Abstract: The Pacific region provides unique opportunities to study human evolution including through analyses of ancient DNA. While some of the earliest studies involving ancient DNA from skeletal remains focused on Pacific samples, in the following 25 years, several factors meant that little aDNA research, particularly research focused on human populations, has emerged. This paper briefly presents the genetic evidence for population origins, reviews what ancient DNA work has been undertaken to address human history and evolution in the Pacific region, and argues that the future is bright but research requires a collaborative approach between academic disciplines but also with local communities.